Decision Making in Selecting Mobile Payment Systems - Chaiyasoonthorn, Wornchanok (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Thailand is transforming its economy into a digital economy. Mobile payment (m-payment) is a core technology that helps the country phases from the manu-facturing-based economy into the digital economy. However, a question remains what factors influencing people to adopt mobile payment. Little literature focuses on users in Thailand. This study aims to determine factors associating with the decision-making process in selecting m-payment systems of respondents in Bangkok. The study addresses a research question. What do factors segregate m-payment adoption? 820 respondents were asked by using a questionnaire. Em-ployment of confirmatory factor analysis (CFA) developed the measurement showing acceptable validity and reliability. The study uses multinomial logistic regression to classify Technology Choices (TCs). The results show low values of Pseudo R-Square, indicating that there is a lack of practical variables. Discus-sions and suggestions are addressed in this research.